2009
DOI: 10.1097/aln.0b013e3181a9160e
|View full text |Cite
|
Sign up to set email alerts
|

QX-314 Produces Long-lasting Local Anesthesia Modulated by Transient Receptor Potential Vanilloid Receptors in Mice

Abstract: We have confirmed in a sensory blockade model that QX-314 is a local anesthetic with a slow onset and a long duration of reversible blockade. Capsaicin, a transient receptor potential vanilloid receptor agonist, accelerated QX-314's onset kinetics, whereas capsazepine, a transient receptor potential vanilloid receptor antagonist, decreased QX-314's efficacy. These observations raise the possibility that endovanilloids may modulate cell entry of QX-314.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Cinnamaldehyde (a TRPA1 agonist) activates TRPA1 and renders it permeable to QX-314 (Lennertz et al, 2012). This approach is very similar to (although probably less effective than) that previously described to silence TRPV1 + afferents by a combination of capsaicin and QX-314 (Binshtok et al, 2007;Ries et al, 2009) since TRPA1 is less permeable to QX-314 than TRPV1 (Nakagawa and Hiura, 2013).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 54%
“…Cinnamaldehyde (a TRPA1 agonist) activates TRPA1 and renders it permeable to QX-314 (Lennertz et al, 2012). This approach is very similar to (although probably less effective than) that previously described to silence TRPV1 + afferents by a combination of capsaicin and QX-314 (Binshtok et al, 2007;Ries et al, 2009) since TRPA1 is less permeable to QX-314 than TRPV1 (Nakagawa and Hiura, 2013).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 54%
“…However, we have recently shown in animal models in vivo that QX-314 produces long-lasting nociceptive, sensory, and motor blockade with a slow onset when administered extracellularly as a peripheral local anesthetic. 5,6 As quaternary agents do not rapidly penetrate biological membranes or the blood-brain barrier, QX-314 may represent a local anesthetic with decreased systemic toxicity compared with conventional tertiary aminoamines. In order to test this hypothesis, we conducted an in vivo animal study in mice to compare QX-314 with lidocaine in terms of its relative potencies for systemic central nervous system (CNS) and cardiac toxicity.…”
Section: Résumémentioning
confidence: 99%
“…Taken together, our current findings and the results of recent studies indicate that the TRPV1 channel represents both a novel LA target and pathway for these agents to reach their intracellular binding site on the voltagegated Na ϩ channel. 8,9,28 In conclusion, we show in this work involving experiments on Xenopus laevis oocytes and tsA201 cells that the quaternary lidocaine derivative, QX-314, behaves as a biphasic regulator of expressed human TRPV1 channels. At low micromolar concentrations, QX-314 inhibits TRPV1 activation in the presence of capsaicin, whereas at higher concentrations in the millimolar range more relevant to clinical regional anesthesia and neural blockade, QX-314 is a TRPV1 channel agonist similar to lidocaine.…”
Section: Pain Medicinementioning
confidence: 99%
“…8 Additional pharmacologic exploration of this possibility confirmed that coapplication of QX-314 with the TRPV1 agonist, capsaicin, significantly accelerates the onset of sensory blockade attributable to QX-314. 9 However, direct mechanistic insight into the interaction of QX-314 with TRPV1 has been lacking.…”
mentioning
confidence: 99%